Resin Nanoceramic CAD/CAM Restoration of the Primary Molar: 3-Year Follow-Up Study - Akif Demirel; Tuğba Bezgin; Funda Akaltan; Şaziye Sarı (Hindawi Limited, 2017)
This case report presents the clinical use of a resin nanoceramic CAD/CAM restoration of a primary second molar without successor in the form of a permanent second premolar tooth in a patient. Three-year follow-up of the case revealed that resin nanoceramic CAD/CAM restoration of the primary molar without successor achieved both aesthetics and function. Despite the high cost of treatment, this type of restoration should be considered if the retained tooth is expected to maintain functionality over the long term.